2013
DOI: 10.1161/atvbaha.112.300226
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Participates in Aortic Valve Calcification in Hypercholesterolemic Animals

Abstract: Objectives— Aortic valve (AV) calcification occurs via a pathophysiological process that includes lipoprotein deposition, inflammation, and osteoblastic differentiation of valvular interstitial cells. Here, we investigated the association between endoplasmic reticulum (ER) stress and AV calcification. Approach and Results— We identified ER stress activation in AV of patients with calcified AV stenosis. We generated an AV calcification mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 60 publications
7
69
0
Order By: Relevance
“…As expected, KDEL, an ER stress marker, 11 was exclusively overexpressed in the myocardium of infected mice ( Figure 1A and 1B). In parallel with the increased expression of the heart failure marker, ANP, Western blot analysis further confirmed the induction of ER stress by assessing the activation of 3 branches of UPR, PKR-like endoplasmic reticulum kinase, inositol-requiring enzyme 1α, and activation of transcription factor 6 26 7 days pi ( Figure 1C-1G).…”
Section: Er Stress Is Activated In Cvb3-induced Avmcsupporting
confidence: 83%
See 1 more Smart Citation
“…As expected, KDEL, an ER stress marker, 11 was exclusively overexpressed in the myocardium of infected mice ( Figure 1A and 1B). In parallel with the increased expression of the heart failure marker, ANP, Western blot analysis further confirmed the induction of ER stress by assessing the activation of 3 branches of UPR, PKR-like endoplasmic reticulum kinase, inositol-requiring enzyme 1α, and activation of transcription factor 6 26 7 days pi ( Figure 1C-1G).…”
Section: Er Stress Is Activated In Cvb3-induced Avmcsupporting
confidence: 83%
“…8,9 To date, studies have indicated that excessive activation of ER stress/CHOP signaling is associated with various cardiovascular diseases, including atherosclerosis, vascular and valvular calcification, myocardial reperfusion injury, and heart failure. [10][11][12] Previous studies have demonstrated the important role of ER stress in viral infection. 13 Viruses can induce ER stress either through overwhelming protein production, or directly disrupting ER stress signaling to facilitate virus replication and pathogenesis.…”
mentioning
confidence: 99%
“…Recent evidence is emerging that ER stress contributes to the pathogenesis of vascular calcification (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). The ER is a major site for the regulation of calcium and lipid homeostasis (11).…”
Section: Introductionmentioning
confidence: 99%
“…As a classical ER stress inhibitor, TUDCA has been proven to decrease the expression of phosphorylated eIF2α and ATF4 (16)(17)(18)(19)(20)(21)(22). In a recent study, Zhejun Cai et al (23), found that TUDCA protected against oxLDL-induced ER stress in VICs, significantly suppressed osteoblastic differentiation and protected against hypercholesterolemia-induced AV calcification in animal models. Therefore, in our study, we also investigated the effect of TUDCA on ER stress response mediated PERK-eIF2α-ATF4 pathway in an in vitro model for ectopic ossification, found TUDCA significantly suppressed the expression of phosphorylated eIF2α and ATF4, and the result is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…TUDCA has been widely used in treatment of disease, such as, cholelithiasis, cholestatic liver disease, diabetes mellitus, obesity, and atherosclerosis, it works via preventing ER stress, as a classical ER stress inhibitor (17)(18)(19)(20)(21)(22). Studies have demonstrated that TUDCA could markedly prevent Aortic valve (AV) calcification, and attenuate AV osteoblastic differentiation in both rabbit and mouse models of AV calcification via inhibition of ER stress and could suppress oxidized low density lipoprotein (oxLDL)-induced osteoblastic differentiation in cultured valvular interstitial cells (VICs) (23) and could alleviate advanced glycation end product-induced apoptosis and osteoblastic differentiation of stromal cells via alleviating ER stress (22,24).…”
Section: Introductionmentioning
confidence: 99%